Role of Foundation Chairman in Program Planning, Facility Management, and Influence on Teacher Performance at MA Darul Muhsinin NWDI Sakra - Nasrullah, Nasrullah (Pendidikan Agama Islam STIT Palapa Nusantara, 2025)
This study addresses the limited research on the leadership role of foundation chairmen in Islamic boarding school-based educational institutions, particularly concerning their impact on teacher performance. The primary objective is to examine the role of the foundation chairman of MA NWDI Montong Kubur Sakra in program planning, office facility management, and the subsequent effects on teacher performance. Employing a descriptive qualitative approach with an intrinsic case study design, the research involved 12 purposively selected participants, including the foundation chairman, the school principal, and ten teachers. Data were gathered through in-depth interviews, participatory observation, and documentation, and analyzed using the interactive model developed by Miles, Huberman, and Saldaña. The results demonstrate that the foundation chairman exercises collaborative, visionary, and transformational leadership. He actively contributes to annual work plan development, facilitates teacher workshops, mentors new educators, initiates reflective leadership forums, and ensures the systematic planning and maintenance of office facilities. This leadership approach has significantly enhanced teacher motivation, professionalism, discipline, and institutional involvement, thereby promoting a sustained culture of educational excellence. The study enriches the discourse on leadership within Islamic education and suggests the broader adoption of participatory leadership practices in similar institutional contexts.